Tissue microarrays of bone marrow aspirate clot allow assessment of multiple samples - Domeny-Duarte, Pollyanna [UNESP]; Niero, Ligia [UNESP]; Custodio Domingues, Maria Ap [UNESP] (Elsevier B.V., 2020)
Time optimization and cost reduction without quality loss is fundamental for scientific production. The TMA technique allows large-scale analysis of paraffin-embedded and fixed tissues using non-decalcified bone marrow specimens. Cytoinclusion samples (n = 264) were selected from patients diagnosed with monoclonal gammopathy (n = 189) at Botucatu Medical School, Sao Paulo State University. Slides were cut from the TMA block and stained with H&E and immunohistochemical markers. Of the 276 fragments included in the receptor block, 45 core detachments were observed, thus 84% of the samples remained viable. The representative material allowed for adequate analysis of isolated cells, which showed nuclear, cytoplasmic and membrane staining. Thus, we verified that inclusion of bone marrow aspirate clot is a valid alternative for TMA histological and immunohistochemical analyses.
Keywords: TMA; Bone marrow clots; Immunohistochemistry